Fiscal policy efficiency and its role in the optimal allocation of resources Study of the Algerian case - harag, masbahe (Milev Journal of Research and Studies, 2016)
Fiscal policy is among the most important tools for managing the economy of the state, either developed or developing countries are using it to achieve economic growth and stability. In this paper, we will discuss the issue of fiscal policy in both axes, tax policy and public spending, and that by addressing the mechanisms that was provide effective fiscal policy allocation which ensures the optimal allocation of resources, and achieve economic growth and equilibrium. At the end, we provide the most important characteristics of the Algerian fiscal policy to conclude finally with some recommendations that may lead to the rationalization of the public spending and finance